Testing statistical assumptions in research - Verma, J P; Abdel-Salam, G; Abdel-Salam (Doha, Qatar : Wiley, 2019)
The book "Testing Statistical Assumptions in Research" provides a comprehensive guide for researchers to ensure the validity of their statistical analyses. It emphasizes the importance of checking assumptions before applying statistical tests, offering step-by-step procedures and explanations of how to do so. The book covers a wide range of statistical concepts, including hypothesis testing, statistical errors, power, sample size, and effect size. It also introduces SPSS functionality and demonstrates how to handle data, draw samples, and create variables. Additionally, the book discusses assumptions for different survey studies and emphasizes the importance of survey design for accurate reporting. By providing examples using SPSS and highlighting the adverse effects of violating assumptions, the book equips readers with the knowledge and tools necessary to conduct reliable and meaningful statistical analyses.
Includes appendix, bibliographical references (p. 203-207) and index.
Keywords: Mathematics And Statistics